2022
DOI: 10.1017/cts.2022.511
|View full text |Cite
|
Sign up to set email alerts
|

Continued impact of COVID-19 pandemic on clinical and translational science early-career researchers

Abstract: This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…CRCs have been major sites of support for early career investigators who conduct patient-oriented clinical research. The majority of CRCs responding to our survey reported that their early career investigators experienced significant challenges in continuing their research, confirming earlier reports [ 12 14 ]. It is hoped that these challenges will abate, but longer-term effects of the pandemic on career development should be monitored, with consideration of strategies to reverse this impact.…”
Section: Discussionsupporting
confidence: 89%
“…CRCs have been major sites of support for early career investigators who conduct patient-oriented clinical research. The majority of CRCs responding to our survey reported that their early career investigators experienced significant challenges in continuing their research, confirming earlier reports [ 12 14 ]. It is hoped that these challenges will abate, but longer-term effects of the pandemic on career development should be monitored, with consideration of strategies to reverse this impact.…”
Section: Discussionsupporting
confidence: 89%
“…In total, 58% of scholars and trainees were unable to conclude their research as initially planned, 57% experienced a dip in productivity, 54% faced escalating competing demands for their time, and 48% had reduced access to vital resources. 3 These disruptions presented significant hurdles for the successful development and sustenance of RTEs. The impact of the pandemic on RTEs also posed downstream effects with individual student trainee’s RSE, or the level of confidence students feel in working within the RTE.…”
Section: Disruptions In Research Training: Lessons From the Covid-19 ...mentioning
confidence: 99%